A framework to eliminate developer involvement in dynamicreporting system / Imran Md Jelas - Md Jelas, Imran (Universiti Teknologi MARA, Perak, 2018)
General dynamic reporting system is used to display general tabulated data to users. Building a general dynamic reporting system is a tedious and time-consuming process. In this paper, we proposed a framework to eliminate a developer involvement in a dynamic reporting system. We proposed a dynamic reporting system to be developed in three separated modules namely: i. table manipulation module, ii. data manipulation module and iii. reporting module. Finally, in this paper we focus on designing the generic master table for table manipulation module namely master_table and master_column.